Perlindungan Hukum Terhadap Pemilik Tanah Atas Pendirian Tiang Listrik Yang Dilakukan Oleh PT. Perusahaan Listrik Negara (Persero) (Studi Kasus: Putusan Perkara No. 4/Pdt.G/2023/PN Mbo) - Gilang Ramadhan; Suardi (PT. Hasba Edukasi Mandiri, 2025)
One of the efforts to improve general welfare is the development of electricity supply. Law Number 30 of 2009 concerning Electricity which has been amended through Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation which has been stipulated through Law Number 6 of 2023 is a reference in the mechanism for implementing the provision of electricity in the public interest, wrong the other concerns the rights and obligations in carrying out the business of providing electricity. Electricity service providers have the right to enter public or private places and use them temporarily, this norm creates a potential conflict of interest with someone's ownership of land. Erecting electricity poles on freehold land without the knowledge of the land rights holder can cause many legal and social problems. The method used in this research is normative legal research which is used to solve research problems by elaborating written law with literature studies that focus on legal theories and positive law that apply in Indonesia. The results of this research show that to obtain legal protection for the erection of electricity poles on freehold land, compensation or compensation is provided to land rights holders. So this research will outline several provisions regarding the procedures that should be carried out by electricity service providers in using private land to erect electricity poles for public purposes.